Exploring Scottish family businesses: economy, geography and community. (28th December 2009) - Seaman, Claire; Graham, Stuart; Falconer, Peter; Stepek, Martin
The results from this debate will provide a starting point for future theoretical and action research and a key aim of the proposed discussion paper is to encourage interested parties with diverse expertise to contribute and highlight their interest in future participation. The implications of this debate are profound and will impact upon Scotland in a variety of ways in terms of economic, cultural and community development. The role of those different groups involved – entrepreneurs, policy makers, practitioners, researchers and educators – will be key. The value of this paper lies primarily in its contribution to a debate and the call for further research in an area of key importance to the Scottish and, indeed, the UK economy.